PENGARUH KONTEN INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PAKET UMROH DI PT RIAU WISATA HATI PEKANBARU - Ma’arif, Dimas Rudin Ahmad; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Social Media Marketing is an activity in interactive marketing communication that occurs between companies and customers. The goal is to make sales of products or services that the company has. This research was conducted to determine the effect of digital marketing through social media instagram on purchasing decisions at PT Riau Wisata Hati, Pekanbaru. The research method used in this research is descriptive quantitative with multiple regression analysis techniques. The data instrument test in this study uses the Validity, Reliability, Normality, Autocorrelation of the Research Model, Multicollinearity, Heteroscedasticity, Analysis of the Coefficient of Determination (R) F Simultaneous, T Partial. The results of this study indicate that the Instagram Social Media Marketing Variable has a positive relationship and has a significant effect on purchasing decisions for Umrah packages at PT Riau Wisata Hati. Keywords: Instagram Marketing, Purchasing Decisions.